Indian no more - McManis, Charlene Willing, 1953-2018 (New York : Tu Books, 2019)
When Regina's Umpqua tribe is legally terminated and her family must relocate from Oregon to Los Angeles, she goes on a quest to understand her identity as an Indian despite being so far from home.
School Library Journal starred, September 2019
Kirkus Review, August 2019
4.4
3-6
720L
W
Keywords: Umpqua Indians -- Juvenile fiction; Families -- Juvenile fiction; Indians of North America -- Relocation -- Juvenile fiction; Umpqua Indians -- Fiction; Family life -- Fiction; Indians of North America -- Relocation -- Fiction; Historical fiction